A review on plant metabolite-mediated nanoparticle synthesis: sustainable applications in horticultural crops - Lakhani, Komal G.; Hamid, Rasmieh; Motamedi, Elaheh; Marviya, G. V. (Frontiers in Nanotechnology, 2025)
Global food security is increasingly threatened by climate change and population growth. This particularly affects horticultural crops, which often do not receive sufficient attention despite their significant nutritional and economic value. These crops pose a major challenge for breeding due to their high genetic diversity, long generation cycles, and complex reproductive biology, underlining the need for innovative approaches. The green synthesis of nanoparticles (NPs) using plant metabolites is proving to be a sustainable solution to these challenges. Biogenic nanoparticles, known for their improved biocompatibility and lower environmental impact compared to chemically synthesized (CS) counterparts, offer promising strategies to increase plant productivity, quality, and resilience. Applications of these nanoparticles include nanofertilizers for efficient nutrient delivery, nanopesticides for targeted pest control, and nano-packaging to reduce post-harvest losses. In addition, they function as nano(bio)sensors for the early detection of pathogens to ensure crop health and minimize losses. Recent studies suggest that biogenic nanoparticles can improve the efficiency of CRISPR/Cas9 transfer, which could promote the development of stress-resistant plants in precision agriculture. This review highlights the role of green nanotechnology in horticultural crop improvement, emphasizing the mechanisms by which plant metabolites mediate nanoparticle synthesis and exploring their diverse agricultural applications. By stimulating seed germination, mitigating biotic and abiotic stress, and improving nutrient quality with minimal environmental impact, biogenic nanoparticles hold great promise for revolutionizing horticulture. However, further research is required to optimize their scalability, standardization, and regulatory compliance so that they can be widely used in sustainable agriculture.